Resolution Islah Refer to the Period of Iddah Perspective of Sigmund Freud - Fuad, Anisul; Sugianto, Sugianto (Ann Publisher, 2023)
Divorce is more influenced by the emotional and psychological factors of the litigants so divorce cases between husband and wife are cases that are very closely related to psychological aspects. This research uses the analytical descriptive method and also uses the qualitative-exploratory method. The causes of divorce are more dominated by constant disputes and quarrels, lack of communication, there is a shift in culture that is increasingly open, the weakening of meaning and value in marriage, due to a weak understanding of religious knowledge, and the ends up leaving one of the parties. The scholars agree that such reconciliation is permissible in Islam and is given as a last resort to reconnect the severed inner birth relationship and applies only to wives who are undergoing the period of 'iddah talaq raj'i, i.e. talaq one and two. The conclusion is that the cause of divorce based on the jurisdiction of PA (Religious Courts) throughout Indonesia is more dominated by factors of constant disputes and quarrels, then economic and finally leaving one of the parties. Attempts to re-establish a household after divorce are called reconciliation.